2016
DOI: 10.1016/j.hpb.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Value of E-PASS models for predicting postoperative morbidity and mortality in resection of perihilar cholangiocarcinoma and gallbladder carcinoma

Abstract: The E-PASS models examined herein may accurately predict postoperative morbidity and mortality in proximal biliary carcinoma resection. These models will be useful for surgical decision-making, informed consent, and risk adjustments in surgical audits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
(42 reference statements)
0
23
1
3
Order By: Relevance
“…Estimation of physiologic ability and surgical stress (E-PASS) system is a more recent predicting system developed by Haga et al [ 10 ] According to his following examination studies, E-PASS was reported to have a good death predicting ability in various surgeries including colorectal cancer surgery. [ 11 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of physiologic ability and surgical stress (E-PASS) system is a more recent predicting system developed by Haga et al [ 10 ] According to his following examination studies, E-PASS was reported to have a good death predicting ability in various surgeries including colorectal cancer surgery. [ 11 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…We also used the number of postoperative days until CRP levels decreased to < 1.0 mg/L in order to investigate the improvement outcomes of patients, and the results obtained indicated that a relationship exists between PRS scores and outcomes. Regarding the accuracy of predicting postoperative complications, previous studies demonstrated that E-PASS accurately predicted postoperative mortality in the surgical treatment of hilar cholangiocarcinoma; the AUC to detect in-hospital mortality was 0.842 for E-PASS [ 16 ]. Similar results were obtained in our study; we yielded an AUC value for the CRS to predict postoperative complications that was greater than 0.814 and calculated a cut-off value of 1.01, which was consistent with previous findings [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the accuracy of predicting postoperative complications, previous studies demonstrated that E-PASS accurately predicted postoperative mortality in the surgical treatment of hilar cholangiocarcinoma; the AUC to detect in-hospital mortality was 0.842 for E-PASS [ 16 ]. Similar results were obtained in our study; we yielded an AUC value for the CRS to predict postoperative complications that was greater than 0.814 and calculated a cut-off value of 1.01, which was consistent with previous findings [ 16 , 17 ]. Collectively, the results of the present study and previous findings support E-PASS models, particularly the CRS having a high predictive power in the field of oral and maxillofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: study type (all casecontrol studies); participants (patients who underwent digestive surgery); comparison (any study that compared the E-PASS model between the patients with complications and without complications, or any study that compared the incidence of morbidity and mortality between a high E-PASS CRS group and a low E-PASS CRS group); outcomes (any form of results we were interested in, such as postoperative complications, morbidity, mortality, and overall survival). The postoperative complications expressly referred to any levels of complications classified as Clavien-Dindo, because some studies had unspecified descriptions, while some studies had Clavien-Dindo II/III/IV/V complications (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%